2017
DOI: 10.1515/jelf-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

The communicative needs of Bangladeshi economic migrants: the functional values of host country languages versus English as a lingua franca

Abstract: This article investigates the language skills and the nature of language provision required by economic migrants from Bangladesh working in the Middle East. It focuses in particular on the perceived values of the host country language (Arabic) versus English as a language franca (ELF). While there have been a number of explorations of the value of learning the host country language for migrants in terms of both labour market outcomes and wellbeing, there is a paucity of, and pressing need for, studies investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In Anglophone countries there has been an abundance of research that has demonstrated the advantages of knowing English, such as, economic and health benefits (Seargeant, Erling, Solly, & Hasan Chowdhury, 2017 provide an overview of this research). While this is often the case, because English is a social practice, immigrant advancement depends on multiple socio-economic factors, especially the attitudes of the host community to the immigrants’ language and culture, which in turn can affect learners’ investment in learning English (Norton, 2017; Piller, 2016).…”
Section: Immigrants In Anglophone Countriesmentioning
confidence: 99%
“…In Anglophone countries there has been an abundance of research that has demonstrated the advantages of knowing English, such as, economic and health benefits (Seargeant, Erling, Solly, & Hasan Chowdhury, 2017 provide an overview of this research). While this is often the case, because English is a social practice, immigrant advancement depends on multiple socio-economic factors, especially the attitudes of the host community to the immigrants’ language and culture, which in turn can affect learners’ investment in learning English (Norton, 2017; Piller, 2016).…”
Section: Immigrants In Anglophone Countriesmentioning
confidence: 99%
“…English (a global lingua franca) were the languages mentioned by participants as being most important, but Hindi, Urdu, and (in the case of Singapore) Chinese, Tamil and Malay were also seen as valuable assets for daily communication and rapport building. In a related study (Seargeant et al, 2017), we found that both Arabic and English had important functional values for the participants, but that these varied depending on interlocutors, domains of work and contexts of situation. For example, the participants who viewed English as being integral to success tended to work in businesses staffed by employees from different language backgrounds who often relied on English as the lingua franca.…”
Section: The Role Of Language Skills In Economic Migrationmentioning
confidence: 71%
“…Heller 2010) that contribute to economic gain. Few studies investigate the value of English qualitatively, or its perceived value as a lingua franca for migrants to countries with other dominant national languages (but see Guido, 2008;Seargeant et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Chovancová, 2014), in this case, teacher's task to assist students to engage with their professional communities by providing the linguistic needs and they can be such as valuable feedbacks for syllabus design and improvements. Research investigating about this roles are many, for example (Cabinda, 2013;Chostelidou, 2010;Hu, 2017;Menggo, Suastra, Budiarsa, & Padmadewi, 2019;Moslemi, Moinzadeh, & Dabaghi, 2011;Seargeant, Erling, Solly, & Chowdhury, 2017) The innovation was implemented in order to improve the current syllabus and more effectively to accomplish the goals of English language teaching in this Institute. Although the current syllabus is relatively sufficient, according to the lecturers involved, it is not entirely practical in terms of topic arrangement and is apparently difficult to implement in classroom teaching.…”
Section: A Study On Students' Needs In Learning English For Pharmacy ...mentioning
confidence: 99%